Method for manufacturing and filling containers designed to contain food products
The method uses a laser to create weakening portions in PET containers, addressing the inflexibility and high costs of existing methods, and achieving efficient and flexible container separation while maintaining high industrial productivity.
Patent Information
- Application Number
- JP2022543514
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-17
- Filing Date
- 2021-01-12
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2041-01-12
AI Technical Summary
Existing methods for manufacturing and filling food containers, particularly those using PET, are inflexible and costly due to the need for frequent blade replacements and the difficulty in forming weakened portions without scissors or cutters.
A method involving the use of a laser to create weakening portions in PET containers by locally reducing the cross-section of connecting edges, achieving a reduction in crystallinity of up to 3% without increasing fragility, allowing for easy separation of containers.
This method significantly reduces maintenance costs, enhances flexibility in changing container shapes and sizes, and maintains high industrial productivity while allowing for practical and simple separation of PET containers.
Smart Images

Figure 0007665634000052 
Figure 0007665634000053 
Figure 0007665634000054
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for the manufacture and filling of containers designed to contain food products. [Background technology]
[0002] Typically, the process for producing and filling a food product comprises: - shaping a sheet (usually made of PS or polystyrene) to provide a number of storage receptacles with at least one access entrance; - filling a receptacle with at least one food product through an access entrance; - sealing the access opening with a closure film or sheet unwound from a roll; - cutting the group of receptacles by means of a blade or cutter; - providing respective weakened and separating portions at the edges for connection between at least two adjacent receiving receptacles of the same group; to provide.
[0003] The step of providing the weakened portion may also be carried out by using a blade or cutter that is normally operated to provide an incision in the connection edge.
[0004] This type of method and the devices used have two drawbacks. The use of cutting blades or cutters to perform the division into groups is not particularly flexible and, at the device level, it is very complicated to change the size of the groups or the extension of the weakened portions.
[0005] These problems are exacerbated by others, especially when one wishes to replace PS with PET to provide a storage receptacle.
[0006] Indeed, in this case the life of the blade or cutter is significantly reduced and the costs incurred are significantly increased.
[0007] Furthermore, when using transparent or colored PET as material, which is characterized by considerable toughness, it is virtually impossible to form weakened portions that would allow separation between the various receptacles by bending them together without the use of scissors or cutters.
[0008] In particular, PET in layered form (i.e., sheets with a thickness of more than 250 microns) with an initial crystallinity of up to 10% is an elastic and tough material, so that in order to create weakened areas at the connection edges between at least two different receiving receptacles by scoring with a cutter, it is necessary to use a system in which the cutters must be closer to each other and score through almost the entire thickness of the material, without nevertheless ensuring the achievement of the intended purpose.
[0009] Furthermore, this embodiment reduces the life of the cutter for application on PET, resulting in higher costs.
[0010] Finally, the process becomes difficult to reproduce. It has been known previously (see the contents of GB 2543495) that the brittleness of PET can be increased by a local increase in crystallinity induced by the action of a laser beam; the thermal effect, an unavoidable consequence of the action of a laser beam on the material it hits, is in fact the cause of the increase in crystallinity.
[0011] It is also known from the literature that crystallization is a process that requires sufficient time and temperature and is induced by prolonged exposure to the action of a low-power laser beam. In this way, the effect of the heating induced by the laser beam is maximized, so that the crystallization temperature range of PET is reached or is reached without the action of the laser resulting in ablation of the specimen, which is obtained while operating at a slow speed [MF Sonnenschein and CM Roland, Appl. Phys. Lett. 57(5), 1990].
[0012] Although it is true that increased crystallinity, and therefore increased brittleness, can be induced in PET by prolonged exposure to low-power lasers, it is also true that this method is not suitable for industrial requirements, which increasingly lead to increased productivity through shorter manufacturing times. Summary of the Invention [Problem to be solved by the invention]
[0013] It is an aim of the present invention to provide a method for the manufacture and filling of containers designed to contain food products, which is capable of improving upon the background art in one or more of the above mentioned aspects.
[0014] Within this goal, it is an object of the present invention to provide a method for the manufacture and filling of containers designed to contain food products, which makes it possible to reduce the maintenance costs of the equipment.
[0015] Another object of the invention is to devise a method for the manufacture and filling of containers designed to contain food products that is extremely flexible and makes it possible to easily change the shape of the groups of interconnected containers and weakened parts.
[0016] Another object of the present invention is to provide a method for the manufacture and filling of containers designed to contain food products that is reliable, relatively easy to provide, at a competitive cost, and that maintains the high industrial productivity currently characteristic of the manufacture of PS containers. [Means for solving the problem]
[0017] This aim, as well as these and other objects which will become more apparent hereinafter, are achieved by a method for the manufacture and filling of containers designed to contain food products according to claim 1, optionally comprising one or more of the features of the dependent claims.
[0018] Further features and advantages of the present invention will become more apparent from the description of preferred, but not exclusive, embodiments of the method for the manufacture and filling of containers designed to contain food products according to the invention, shown as non-limiting examples in the accompanying drawings, in which: [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic diagram of an apparatus for the manufacture and filling of containers designed to contain food products. [Diagram 2] FIG. 2 is a top view of a container provided by the method according to the invention; [Diagram 3] FIG. 3D relief of the surface opposite the laser acting surface, acquired with ZYGO high definition optics. The relief obtained in three areas of the specimen shows that in the weakened areas there are tension variations (induced by the laser irradiation step) that lead to surface depressions. [Figure 4] FIG. 3D relief of the surface opposite the laser acting surface, acquired with ZYGO high definition optics. The relief obtained in three areas of the specimen shows that in the weakened areas there are tension variations (induced by the laser firing step) which lead to surface misalignment. [Diagram 5] FIG. 1 shows a specimen on the left with a continuous weakened portion and on the right with a weakened portion with a through opening. The specimens were viewed in polarized light, and only the heat, not the laser beam, reached. The change in tension state in the immediate vicinity of the laser action is clearly evident. [Figure 6] A diagram of three images of a superficial weakened area, the 3.5x magnification image clearly shows the entire incision, the 16x magnification image shows the edges of the incision and in the center the incision trough (which is the subject of analysis), and the 56x magnification image shows only the incision trough where analysis is to be performed. [Figure 7]FIG. 3 shows three images of a superficial weakened area, the 3.5x magnification image clearly shows the entire incision, the 16x magnification image shows both the through opening and the "bridge", and the 32x magnification image highlights the "bridge" of the weakened area where analysis should be performed. [Figure 8] FIG. 13 is an image of a surface defect of a test specimen with known thermal history. [Figure 9] The overlay of Raman microscopy spectra is shown, where the spectrum indicated by A has a clear fluorescence signal in the range of 1000-2050 cm and therefore must be excluded. [Figure 10] Shown is an overlay of Raman microscopy spectra of maximum intensity variations in the range 1800-2050 cm-1. The spectrum denoted by B is an example of an acceptable spectrum with a maximum intensity variation of less than 150, while spectrum C is instead unacceptable as it has a maximum intensity variation of more than 150. [Figure 11] 1 is a magnified image of holes formed in the specimen after analysis by Raman microscopy. [Figure 12] An example of the treatment of the cold crystallization peak in the second scan of the calorimetry is shown. [Figure 13] An example of the processing of melting peaks in the second scan of the calorimetric analysis is shown. [Figure 14] An example of a cross-sectional analysis of a specimen with known thermal history is shown. [Figure 15] The analytical conditions set in the Omnic software for the acquisition of Raman spectra are shown and are further detailed herein. [Figure 16] The analytical conditions set in the Omnic software for the acquisition of Raman spectra are shown and are further detailed herein. [Figure 17] The analytical conditions set in the Omnic software for the acquisition of Raman spectra are shown and are further detailed herein. [Figure 18] 1 shows an example of the analysis of a Raman spectrum by peak resolution function according to the methods detailed herein. [Figure 19] The processed calibration line for pot 1 is shown, including the equation of the line and the value of R2. [Figure 20] The processed calibration line for Pot 2 is shown, including the equation of the line and the value of R2. [Figure 21] 1 shows the calibration straight line processed for 1 mm PET sheet, including the equation of the line and the value of R2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] With reference to the drawings, a method for the manufacture and filling of containers designed to contain food products according to the present invention comprises the steps of: - forming a sheet 10 of PET (polyethylene terephthalate) to provide a plurality of storage receptacles 11 with at least one access entrance 12, the PET sheet having an initial crystallinity of 10% or less; - filling a receptacle with at least one food product through an access entrance; - sealing the access opening 12 by a closure film 13; providing a weakened portion 21 at a connection edge 22 between at least two adjacent receiving receptacles 11; Includes.
[0021] In particular, the step of providing the weakened portion 21 comprises the step of emitting a laser beam 40 at at least a portion of the connecting edge 22 in order to bring about a local reduction in the cross section of the connecting edge 22 along the weakened portion 21 .
[0022] By way of example, the local reduction in cross section is at least equal to 50% relative to the initial cross section, preferably at least equal to 70% and even more preferably at least equal to 80%.
[0023] According to the invention, the final crystallinity in the weakened portion 21 after the laser beam 40 irradiation step is equal to or up to 3% lower or higher than the crystallinity of the portion of the connection edge 22 that is not affected by the modifications resulting from the laser beam 40 irradiation step and the sealing step.
[0024] In fact, as will become apparent from the tests described below, the crystallinity of the portion of the connecting edge 22 that is not affected by the changes resulting from the steps of applying the laser beam 40 and sealing substantially corresponds to the crystallinity of the sheet 10.
[0025] In practice, the radiation step is carried out at a certain speed and power at the connection edge at the end of the step, for example to determine:
[0026] - Reduced crystallinity, -Maintaining a similar degree of crystallinity, or -Up to 3% increase in crystallinity.
[0027] The degree of crystallinity after the radiation step is assessed substantially in the weakened portion 21 . In particular, the step of providing the weakened portion 21 comprises the step of emitting a laser beam 40 originating from a laser having a power at least equal to 250W.
[0028] Advantageously, the laser emits at a wavelength absorbed by PET, and by way of example it is possible to use a CO2 laser having a wavelength equal to 10.6 microns, 10.2 microns or 9.3 microns.
[0029] Laser radiation occurs at least in a portion of the connection edge 22 in order to bring about a local reduction in the cross section of the connection edge 22 along the weakened portion 21 .
[0030] A local reduction in cross-section is understood to mean not only a reduction in the cross-section of the connecting edge 22 that is substantially constant along the longitudinal extension of the weakened portion 21, but also the provision of a plurality of through-openings that pass through the connecting edge and are spaced apart from one another to provide the weakened portion 21.
[0031] The reduction in cross section along the connecting edge 22 can also provide through openings alternating with a constant reduction in thickness or with different thickness reduction sequences.
[0032] Surprisingly, it was found that the radiation step does not result in an increase in crystallinity (more than 3%), but the weakened portion 21 is able to ensure a very effective break along the connection edge 22 between two adjacent receiving receptacles 11.
[0033] Advantageously, the thickness of the connecting edge 22, on which the step of providing the weakened portion 21 is carried out, is between 300 microns and 1800 microns, more preferably between 700 microns and 1300 microns.
[0034] Advantageously, between the sealing step and the step of providing the weakened portion 21 there is a step of separating the receiving receptacles 11 within the group 31 of receiving receptacles 11 .
[0035] Preferably, this separation step is performed by a laser beam designed to make a cut 30 in the connecting edges between the receiving receptacles 11.
[0036] At the end of the method according to the invention, a group 31 of receiving receptacles 11 (known as a multipack) is obtained, each weakened portion 21 being formed between adjacent receiving receptacles 11 of the same group 31 and adapted to enable separation of each receiving receptacle 11 from the other receiving receptacles 11 of the same group 31.
[0037] The use of a laser to provide the weakened portions 21 makes the method according to the invention very flexible, since it can be easily programmed if the size of the receiving receptacle 11 or the shape of the groups 31 changes.
[0038] The providing step includes the step of emitting a laser beam with a power of greater than 250 W, preferably less than 1500 W, at a speed of 15 m / min to 170 m / min, more preferably with a power of 300 W to 1200 W, at a speed of 20 m / min to 144 m / min.
[0039] In this regard, an attempt has been made to verify whether the control of the operating conditions of the laser (in terms of power and speed) can actually affect the final crystallinity in an experimentally controllable manner (by determining non-variation or a maximum decrease or increase of 3%), and therefore to identify optimal operating conditions and parameters to obtain both very easy breakage, resulting in a decrease in the toughness of the connection edges, and to implement a process that can ensure sufficient productivity.
[0040] For this reason, a series of experiments was carried out. First, the variation in crystallinity of the specimens subjected to laser radiation was investigated.
[0041] The use of a laser beam with a power of more than 250 W, without significantly increasing the crystallinity, makes it possible to change the distribution of tension within the PET, thus resulting in an increase in its brittleness.
[0042] The very rapid action of the powerful laser acting locally minimizes thermal effects and leaves the areas adjacent to the weakened section 21 unchanged, thus resulting in a change in the tension of the polymer chains, thereby weakening the PET at the weakened section without causing a significant increase in crystallinity.
[0043] The laser acts on the face of the connection edge 22 which is directed upwards, i.e. facing away with respect to the receiving receptacle 11 .
[0044] Furthermore, the method according to the invention provides for a sterilization step to be performed upstream or downstream of the thermoforming step.
[0045] The method further provides for performing a step of extracting gas and volatile materials during the radiating step.
[0046] This extraction step makes it possible to remove gases and volatile substances from the emission area, but at the same time makes the action of the laser more efficient.
[0047] In accordance with the present invention, it is possible to provide for the use of dyes or pigments by mass that eliminate or reduce transparency from the finished PET sheet.
[0048] Furthermore, there is nothing preventing the use of recycled or partially recycled PET. The present invention therefore describes an alternative method for weakening PET without resorting to common crystallization methods, and indeed it is observed that in the weakened areas 21 there are local variations in crystallinity that are an increase of less than 3% relative to areas not affected by the laser.
[0049] As already mentioned, this variation in the tension of the material can be assessed indirectly by using appropriate techniques for surface analysis and observation of the specimen with polarized light.
[0050] It is known in the literature that the occurrence of deformations in the specimen can be associated with changes in the tension state. The acquisition of the surface contour, carried out with Zygo, a high-precision optical instrument for detecting 3D surfaces, made it possible to observe that deformations such as surface indentations or inconsistencies can occur in weakened areas on the specimen surfaces not directly exposed to the action of the laser but opposite it.
[0051] Also, observation of the weakened specimens under polarized light made it possible to highlight the change in the tensile state of the material in the immediate vicinity of the action of the laser light, where only the heat of the beam reached it.
[0052] In this regard, it has been found experimentally that on the opposite side to the action of the laser, the material subjected to the thermal effect of the laser will attempt to rearrange itself and remain bonded to the "cold" material.
[0053] The determination of the crystallinity of a polymer has been the subject of much discussion, and there are many techniques for determining it.
[0054] X-ray diffraction and calorimetry techniques based on differential scanning calorimetry (hereinafter referred to as "DSC") are the most widely used techniques for determining the crystallinity of polymer specimens, but issues such as specimen preparation, analysis time, accuracy and complexity of data analysis, and in the case of X-ray diffraction, the high cost of the technique have made the use of Raman microscopy, which further allows for faster analysis and is a non-destructive technique, favorable.
[0055] However, Raman spectroscopy is not a self-sufficient technique and requires the construction of a calibration curve and correlation with other methods to measure crystallinity [V. Shabafrooz et al. SPE ANTECTM Indianapolis 2016].
[0056] In the analyses reported below, the technique of Raman spectroscopy on a microscopic scale (hereafter referred to as “Raman microscopy”) was used, since it is a useful technique for spot analysis of the specimens and can further localize weakened areas.
[0057] Raman microscopy was then correlated with the DSC calorimetry technique by constructing an appropriate calibration curve with the crystallinity (Xc(%)) calculated by DSC on the horizontal axis and the values obtained by Raman microscopy on the vertical axis.
[0058] For this purpose, specific test specimens were prepared with known thermal histories. Calibration curves, as well as test specimens with known thermal history, should be prepared whenever materials with different properties (different intrinsic viscosities (IV), different thicknesses, different additives, ...) are studied.
[0059] Calorimetric analyses were performed using a Perkin Elmer DSC8500 differential scanning calorimeter equipped with a CLN2 liquid nitrogen cooling system, Pyris processing software, and the direction of the endothermic transition toward positive values on the vertical axis. For each analysis, specimens in amounts of 7 to 15 mg were weighed into manually closed non-airtight specimen holders. The specimens underwent no pretreatment prior to the analyses, and they were all performed in a nitrogen flow (20 mL / min).
[0060] The instrument was used for two purposes: 1) To prepare specimens with known thermal histories for subsequent analysis by Raman microscopy; 2) To prepare test specimens with known thermal histories similar to the previous ones and calculate their crystallinity by DSC calorimetry.
[0061] In each case, areas of the finished container not affected by thermoforming were sampled to prepare test specimens with known thermal histories.
[0062] With reference to the dual purpose of using the DSC tool, a distinction is made between the analytical conditions below. 1) Preparation of specimens with known thermal histories to be analyzed by Raman microscopy: a. 1st scan (1 scan): 30℃~300℃, 20℃ / min; b.Isotherm: 300°C for 1 min; c. Cooling: 300°C to 0°C, X°C / min, X=20, 50, 100, quench obtained by selecting "Ballistic cooling to temperature" setting; 200.
[0063] 2) Regarding the preparation of similar specimens with known thermal histories that are processed to obtain crystallinity from DSC: a. 1st scan (1 scan): 30℃~300℃, 20℃ / min; b.Isotherm: 300°C for 1 min; c. Cooling: 300°C to 0°C, X°C / min, X=20, 50, 100, quench obtained by selecting the "Ballistic Cool to Temperature" setting; 200 d. Second scan (2 scans): 0°C~300°C, 20°C / min; The analytical conditions thus set make it possible to eliminate the thermal history of the specimen with melting from the first scan. Cooling at a controlled and defined rate (20; 50; 100; quench; 200 °C / min) gives specimens with increasing crystallinity as the cooling rate decreases. Specimens for subsequent Raman analysis and those that have also been subjected to a second heating should therefore be considered similar for equal cooling rates. The former were directly analyzed by Raman microscopy, while the latter, in analytical conditions, also received a second heating from the treatment, with the crystallinity by DSC occurring during cooling. This value must correlate with the Raman microscopy value calculated for that similar specimen.
[0064] Since the processing procedure for the calculation of crystallinity is carried out on the second heat, the instrument was calibrated to heat and cool at 20° C. / min, as recommended for PET analysis [A. Hammer, Thermal analysis of polymers. Part 1: DSC of thermoplastics, Mettler Toledo UserCom 31].
[0065] Determination of the crystallinity of specimens with known thermal history by DSC was performed by processing the second scan (2 scans). The melting and cold crystallization peaks were processed to derive the heat of fusion and crystallization values. The processing was performed by proceeding as follows, so that the integrated baseline matched the baseline of the particular thermogram: the absolute value of the heat of crystallization (cold crystallization in 2 scans) normalized to the specimen mass (ΔHcc) was subtracted from the heat of fusion normalized to the specimen mass (ΔHf) and the result was matched to the tabulated value of ΔHf° for PET (140 J / g), which is the theoretical value of the heat of fusion normalized to the mass of 100% crystalline PET, determined by the indirect method using the Flory equation described below: Xc after cooling (%)=(ΔH f -|ΔH cc |)*100 / 140 [''Polymer Heat of Fusion'', Thermal applications note, R.L. Blaine, G. Ellis et al., Spectrochimica Acta Part A, 1995, vol.51, 2139-2145. The equation used is as follows: V. Shabafrooz et al. SPE ANTECTM Indianapolis 2016].
[0066] For spectroscopic analysis, the technique of Raman microscopy was employed by using a Thermo Fisher DXR Raman microscope.
[0067] In Raman spectroscopy applied to PET, it is known that there are active molecular vibrations at specific Raman shifts, whose signals have an intensity or shape that depends on the crystallinity of the specimen [SG Kazarian, N.H. Brantley, CA Eckert, Vibrational Spectroscopy 19, 1999, 277-283A Study of Polymer Crystallinity Using the RamanStation 400F, www.perkinelmer.com; J.S. Rossier et al., Langmuir 15, 1999, 5173-5178, G. Ellis et al., Spectrochimica Acta Part A, 1995, vol. 51, 2139-2145; J.C. Rodriguez-Cabello et al., Journal of Raman spectroscopy, vol. 25, 1994, 335-34].
[0068] In the tests carried out, vibrations corresponding to the stretching of carbonyl groups were analyzed, the band width of which decreases with increasing crystallinity of the analyzed specimen.
[0069] 1700cm -1 ~1760cm -1We calculated the full width half height (FWHH) of the band associated with this vibrational motion, which occurs in the Raman shift range of 100 nm [JC Rodriguez-Cabello et al., Journal of Raman spectroscopy, vol. 25, 1994, 335-34].
[0070] For specimens submitted to analysis by Raman microscopy, we distinguish between specimens with known thermal history, prepared by DSC as previously described, and specimens with unknown crystallinity, determined by interpolation of a calibration curve.
[0071] Specimens with unknown crystallinity were in fact analyzed on the surface exposed to the laser action, acquiring spectra at at least three points in the area of interest, in particular three points at the bottom of the incision ("trough") were analyzed in the continuous weakened section, and three points in the solid area equidistant from the through opening ("bridge") were analyzed in the weakened section with the through opening. Alternatively, specimens with known thermal history prepared in DSC were analyzed in their cross-section by Raman microscopy by fixing each specimen in a specific holder (kit provided by ThermoFisher) for cross-sectional analysis, so that the plane of the specimen was fixed in the gripping element. Then, a blade (provided by ThermoFisher) was used to cleanly cut the specimen to obtain a rectangular cross-section centered on the circular specimen, on which the spectral acquisition was performed at at least 10 points.
[0072] The acquisition of the spectra and their processing is instead reported and is valid for all specimens.
[0073] Raman spectra were recorded by setting the following acquisition modes in the "Omnic for Dispersive Raman" software: 1) In the experimental setup acquisition window, select the "Auto Exposure" option, "Desired S / N" equal to 500, "Maximum Collection Time (min)" equal to 5, and "Preview Exposure Time (sec)" equal to 1.
[0074] 2) In the same acquisition window, the final format in which the spectrum is displayed also changes, especially the "shift spectrum (cm -1 ) for "Correction", select the "Fluorescence" option from the drop-down menu, and in the sub-window that opens by clicking once on the word "Fluorescence", select "Use polynomial order: 6" and also select "Cosmic ray threshold: Low", and in the present invention, the spectrum was obtained by further selecting the "Smart background" option available in the same window.
[0075] 3) In the bench window of the experimental setup, select 532 nm as the "Laser Wavelength" (for this wavelength laser the instrument must be properly calibrated), set the "Laser Power" equal to 10 mW (the maximum that can be set for the instrument used), set the "Aperture" equal to a 25 μm pinhole, and set the minimum and maximum acquisition range in the present invention to 200 to 3500 cm. -1 Finally, to accurately analyze the selected points, select the 10x lens in the bench window and use that magnification lens in the optics module to focus the optical image of the area of interest. The "Grating", "Estimated Resolution", "Estimated Spot Size" and "Tolerance" parameters cannot be manually changed by the operator, but depend on the characteristics of the instrument or other parameters set here presented.
[0076] 4) For better control of the spectra collection, it is also recommended to set all controls during collection selectable in the quality window of the experimental setup.
[0077] In the Atlμs window, for each specimen, the "Sample point tool" function was used to select several points (at least 10 for specimens with known thermal history and at least 3 for unknown specimens) from which spectra will be acquired. The points must be selected such that for each point the image is in focus and care must be taken to avoid surface defects; furthermore, for specimens with known thermal history, the distance between the points must be approximately constant and the sequence must cover the entire longitudinal length of the previously obtained rectangular cross section, care must be taken to avoid bubbles or roughness. Once the points of interest have been selected, it is possible to proceed with the spectrum acquisition by the "Map collection" function.
[0078] It will be appreciated that if it is not possible to use the "Sample Point Tool" function or if problems arise with the continuous acquisition of selected points, it is possible to manually acquire one spectrum at a time, with the general criteria for point acquisition above applying.
[0079] The spectral acquisition mode, as set, interrupts the analysis after 5 min of collection, regardless of whether the desired signal-to-noise ratio has been reached or not. It is therefore necessary to pay attention to the spectra obtained and take into account that a spectrum cannot be considered acceptable if:
[0080] -Raman shift range 1000~2050cm -1 , with signal (peak) or baseline fluctuations (linear to curvilinear) due to fluorescence; - Raman shift range that does not include peaks that may be related to the test specimen (e.g., 1800-2050 cm -1 ) has a maximum variation in intensity (Raman intensity), defined as the difference between the absolute maximum and minimum values in the selected range, of more than 150 units.
[0081] If this situation occurs, here are some recommendations: -Ensure that the area of analysis is in focus; -Ensure that the test specimen is clean and free of dust or grease that may interfere with the analysis; -Change the analysis point.
[0082] It is also possible that following the Raman microscopy analysis, holes form at the analyzed points. This phenomenon can be observed by the Atlμs window and in any case is reported by the software in the "Status collection" window as "Sample is burning". In this case, the analysis point must be changed.
[0083] For the processing of the spectra obtained by Raman we proceeded as follows: 1) In the spectrum, 1820cm to 1640cm -1 A region of was selected and a peak resolution function was chosen for the analysis.
[0084] 2) Analysis was performed using Gaussian / Lorentzian functions in the analysis window opened by the peak resolution function [JC Rodriguez-Cabello et al., Journal of Raman spectroscopy, vol. 25, 1994, 335-344; S. Yang, S. Michielsen, Macromolecules 36, 2003, 6484-6492, with ''sensitivity high'', ''noise target'' of 0.5 and linear ''baseline''].
[0085] 3) 1780~1680cm -1 Once the range was selected, the FWHH value was calculated by clicking the appropriate button.
[0086] The average of the resulting FWHH values was then calculated for all specimens (average over three points for specimens with unknown crystallinity, average over at least ten points for specimens with known thermal history) and used in a method consistent with each specimen: 1) A calibration curve was constructed using the average FWHH of specimens with known thermal history; 2) The average FWHH of specimens with unknown crystallinity were interpolated on the calibration curve to derive their crystallinity.
[0087] The development of the presented analytical method made it possible to analyze points of interest on the specimen in order to verify that the laser beam irradiation step in the weakened area determined a local variation in crystallinity not exceeding 3% relative to the reference crystallinity.
[0088] The standard crystallinity is: Case A) Crystallinity of non-thermoformed PET sheet; Case B) The crystallinity of the semicircular portion of the finished container is determined as follows:
[0089] 1) At least 0.6 mm away from the through cut; 2) at least 0.3 mm away from the weakened area; 3) At least 0.3mm away from the heat seal; Case C) Less preferred, crystallinity in the heat seal ring of the finished container.
[0090] The heat seal ring is included in the reference because it has been shown to represent a non-thermoformed area of the PET container since the sealing operation does not alter the crystallinity of the PET.
[0091] Example 1 Pot 1 - Thickness 1.2mm Using pot 1 with a thickness of 1.2 mm in the area not directly exposed to thermoforming, a calibration curve was constructed which was valid only during testing by preparing test specimens with known thermal history obtained from the non-thermoformed and non-heat sealed parts of pot 1.
[0092] Test specimens with known thermal history were prepared by DSC according to the method set out below: I. Preparation of specimens with known thermal histories to be analyzed by Raman microscopy: a. 1st scan (1 scan): 30℃~300℃, 20℃ / min; b.Isotherm: 300°C for 1 min; c. Cooling: 300°C to 0°C, X°C / min, X=20, quench obtained by selecting the "Ballistic Cool to Temperature" setting; 200 II. Regarding the preparation of similar specimens with known thermal histories that are processed to obtain crystallinity from DSC: a. 1st scan (1 scan): 30℃~300℃, 20℃ / min; b.Isotherm: 300°C for 1 min; c. Cooling: 300°C to 0°C, X°C / min, X=20, quenching obtained by selecting the "Ballistic cooling to temperature" setting; 200; a. Second scan (2 scans): 0℃~300℃, 20℃ / min; The determination of the crystallinity of specimens with known thermal history by DSC was carried out by processing the second scan (2 scans) to calculate the crystallinity due to a cooling step at a defined rate. For this processing, the thermogram of the second scan was taken into account. The values of the heat of fusion (ΔHf) and the heat of cold crystallization (ΔHcc) normalized to the mass of the specimen were determined by setting a "standard" linear integral baseline and integrating the exothermic peak due to cold crystallization and the endothermic peak due to melting. The peaks of fusion and cold crystallization were processed so that the integrated baseline coincided with the baseline of a particular thermogram. By this principle, the melting peak was processed in the temperature range of 210 ° C to 262 ° C and the cold crystallization peak was processed in the temperature range of 137 ° C to 183 ° C only in the case shown in this example. In the case of the specimen cooled at 20 ° C / min, in the second heating, the thermogram did not show a peak due to cold crystallization.
[0093] Figures 12 and 13 show typical process thermograms of the cold crystallization and melting peaks.
[0094] In particular, FIG. 12 is an example of the treatment of a cold crystallization peak in the second scan of the calorimetry, and FIG. 13 is an example of the treatment of a fusion peak in the second scan of the calorimetry.
[0095] For each calorific analysis considered, the following formula was applied: Xc after cooling (%)=(ΔH f -|ΔH cc |)*100 / 140 In this way, the degree of crystallinity is derived from the calorimetry (DSC) of a specimen with a known thermal history.
[0096] Specimens with known thermal histories prepared for Raman microscopy analysis were appropriately sectioned and inserted into an appropriate specimen holder to acquire at least 10 spectra along the longitudinal direction of the section (Figure 14).
[0097] Figures 15, 16 and 17 show images of the analytical conditions set, reported descriptively in the previous chapter.
[0098] Figure 18 shows an example of the processing of spectra obtained with the method described in the previous section. Following processing of each spectrum, the average of the resulting FWHH values was calculated for each specimen. These values, together with the crystallinity of the homologous specimens, obtained by processing the respective thermograms and used to construct the horizontal axis, were used to construct the vertical axis of a calibration curve specific to Pot 1.
[0099] The chart points were then fitted with a linear trend line and that equation was used for subsequent interpolation of FWHH values for specimens of unknown crystallinity originating from pot 1 (and not from any other).
[0100] FIG. 19 shows the calibration straight line including the Pot 1 equation.
[0101] [Table 1]
[0102] For the Pot 1 specimen, the reference area was located in the semicircular portion of the finished pot, since the initial PET sheet was not available: - At least 0.6 mm away from the through-cut; - at least 0.3 mm away from the weakened area; - At least 0.3 mm away from the heat seal area; For the identified portions, three spectra were acquired using a Raman microscope (spectral acquisition and corresponding processing were performed as described above for Raman microscopy) and the average FWHH value was calculated. The average FWHH value was then interpolated on the calibration straight line constructed for pot 1. This allowed the calculation of the baseline crystallinity of pot 1.
[0103] [Table 2]
[0104] Continuous weakening a) A laser with an output of 300 W and a speed of 21 m / min was used.
[0105] The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0106] [Table 3]
[0107] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0108] [Table 4]
[0109] b) A laser with a power output of 750 W and a speed of 77 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0110] [Table 5]
[0111] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0112] [Table 6]
[0113] c) A laser with a power output of 1200 W and a speed of 124 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0114] [Table 7]
[0115] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0116] [Table 8]
[0117] Weakened section with through opening a) A laser with an output of 300 W and a speed of 20 m / min was used.
[0118] The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0119] [Table 9]
[0120] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0121] [Table 10]
[0122] b) A laser with a power output of 750 W and a speed of 45 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0123] [Table 11]
[0124] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0125] [Table 12]
[0126] c) A laser with a power output of 1200 W and a speed of 72 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0127] [Table 13]
[0128] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0129] [Table 14]
[0130] Consideration of heat seal ring In order to precisely define a reference for the subsequent measurement of the crystallinity variation correlated to the laser irradiation step, the heat-sealed ring of pot 1 was studied. In particular, the FWHH values of the top and bottom of the non-thermoformed areas of the pot at the heat-sealed ring were calculated by Raman microscopy and, by interpolation with the calibration straight line, the crystallinity of the points was calculated and compared with that of the reference.
[0131] Again, analysis was performed at three locations, both above and below the heat seal ring.
[0132] [Table 15]
[0133] [Table 16]
[0134] Example 2 Pot 2 - Thickness 1.27mm Using pot 2 with a thickness of 1.27 mm in the area not directly exposed to thermoforming, a calibration curve was constructed that was valid only during testing by preparing test specimens with known thermal history obtained from the non-thermoformed and non-heat sealed portions of pot 2.
[0135] The various steps for constructing the calibration curve have already been presented in detail in Example 1 relating to Pot 1 and do not change in Example 2 for Pot 2, so they will be ignored in the following and it is preferable to focus instead on what was done differently for Pot 2.
[0136] Similar specimens with known thermal history were prepared by cooling from 300° C. to 0° C. at X° C. / min, X=20,100, with a quench obtained by selecting the “Ballistic Cool to Temperature” setting.
[0137] For the analysis of specimens with known thermal history, in particular for the determination of the degree of crystallinity by DSC calorimetry, a melting peak in the temperature range of 210°C to 266°C and a cold crystallization peak in the temperature range of 120°C to 165°C were processed.
[0138] Raman analysis was performed following the procedure given previously without major modifications. For pot 2, the average values of FWHH from Raman microscopy and crystallinity from DSC were fitted with a linear trend line and the equation was used to interpolate specimens with unknown crystallinity from the same pot 2 (but not others).
[0139] FIG. 20 shows the calibration straight line including the Pot 2 equation.
[0140] [Table 17]
[0141] For the Pot 2 specimens, the reference area was located in the semicircular portion of the finished pot, since the initial PET sheet was not available: - At least 0.6 mm away from the through-cut; - at least 0.3 mm away from the weakened area; - At least 0.3 mm away from the heat seal area; For the identified portions, three spectra were acquired using a Raman microscope (spectral acquisition and corresponding processing were performed as described above for Raman microscopy) and the average FWHH value was calculated. The average FWHH value was then interpolated on the calibration straight line constructed for pot 2. This allowed the calculation of the baseline crystallinity for pot 2.
[0142] [Table 18]
[0143] Continuous weakening a) A laser with an output of 300 W and a speed of 22 m / min was used.
[0144] The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0145] [Table 19]
[0146] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0147] [Table 20]
[0148] b) A laser with a power output of 750 W and a speed of 68 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0149] [Table 21]
[0150] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0151] [Table 22]
[0152] c) A laser with an output of 1200 W and a speed of 109 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0153] [Table 23]
[0154] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0155] [Table 24]
[0156] Weakened section with through opening a) A laser with an output of 300 W and a speed of 21 m / min was used.
[0157] The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0158] [Table 25]
[0159] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0160] [Table 26]
[0161] b) A laser with a power output of 750 W and a speed of 55 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0162] [Table 27]
[0163] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0164] [Table 28]
[0165] c) A laser with an output of 1200 W and a speed of 88 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0166] [Table 29]
[0167] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0168] [Table 30]
[0169] Consideration of heat seal ring In order to precisely define a basis for the subsequent measurement of the crystallinity variation associated with the laser irradiation step, the heat-sealed ring of pot 2 was studied. In particular, the FWHH values of the top and bottom of the non-thermoformed areas of the pot at the heat-sealed ring were calculated by Raman microscopy, and by interpolation with the calibration straight line, the crystallinity of the points was calculated and compared with that of the pot.
[0170] Again, analysis was performed at three locations, both above and below the heat seal ring.
[0171] [Table 31]
[0172] [Table 32]
[0173] Example 3 1mm thick PET sheet A calibration curve, valid only for the duration of the test, was constructed using a 1 mm thick sheet of PET by preparing specimens with known thermal histories obtained in parts of the sheet not subjected to laser action.
[0174] It is preferable to note that the various steps for constructing the calibration curve have already been presented in detail in Example 1 with reference to Pot 1 and do not change for PET sheets, so they will be ignored in the following and were instead carried out in a different way for PET sheets.
[0175] Similar specimens with known thermal history were prepared by cooling from 300°C to 0°C, at X°C / min, X=20, 50, 100, 200, with a quench obtained by selecting the "Ballistic Cool to Temperature" setting.
[0176] For the analysis of specimens with known thermal history, specifically for determining the degree of crystallinity by DSC calorimetry, a melting peak in the temperature range of 210°C to 263°C and a cold crystallization peak in the temperature range of 118°C to 185°C were processed.
[0177] Raman analysis was performed according to the procedure previously specified without major modifications. For the 1 mm thick sheets, the average values of FWHH from Raman microscopy and crystallinity from DSC were fitted with a linear trend line and the equation was used to interpolate specimens with unknown crystallinity derived from the same 1 mm sheet (but not others).
[0178] FIG. 21 shows the calibration line including the equation for a 1 mm sheet of PET.
[0179] [Table 33]
[0180] The equation for the calibration straight line thus constructed was used to derive the crystallinity of the reference and weakened parts, verifying that the variation between the two crystallinity degrees was less than 3%.
[0181] Three spectra were acquired with the Raman microscope for the surface of the unexposed PET sheet (the modes of spectral acquisition and associated processing were performed as described above) and the calculated FWHH values were averaged. The average FWHH value was then interpolated on the calibration straight line constructed for the 1 mm PET sheet. This allowed the crystallinity of the unexposed sheet to be calculated.
[0182] [Table 34]
[0183] Continuous weakening a) A laser with an output of 300 W and a speed of 22 m / min was used.
[0184] The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0185] [Table 35]
[0186] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0187] [Table 36]
[0188] b) A laser with a power output of 750 W and a speed of 32 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0189] [Table 37]
[0190] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0191] [Table 38]
[0192] c) A laser with a power output of 1200 W and a speed of 92 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0193] [Table 39]
[0194] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0195] [Table 40]
[0196] Weakened section with through opening a) A laser with an output of 300 W and a speed of 20 m / min was used.
[0197] The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0198] [Table 41]
[0199] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0200] [Table 42]
[0201] b) A laser with a power output of 750 W and a speed of 25 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0202] [Table 43]
[0203] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0204] [Table 44]
[0205] c) A laser with a power output of 1200 W and a speed of 58 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at three solid regions (known as "bridges") of the weakened section, at points substantially equidistant from the through opening.
[0206] [Table 45]
[0207] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0208] [Table 46]
[0209] Example 4 1mm thick PET sheet Low power and low speed testing To verify the effect of the action of a low power laser (power less than 250 W) acting on a PET sheet at low speed (speed less than 15 m / min), the following test was carried out.
[0210] The specimens tested were similar to those presented in the previous Example 3, therefore the calibration straight line constructed and shown for the specimens of Example 3 was also valid for the considered Example 4 to verify whether the variation between the crystallinity of the reference area and the weakened area was less than 3% and was used in the calculations reported below.
[0211] Three spectra were acquired with the Raman microscope for the surface of the unexposed PET sheet (the modes of spectral acquisition and associated processing were performed as described above) and the calculated FWHH values were averaged. The average FWHH value was then interpolated on the calibration straight line constructed for the 1 mm PET sheet. This allowed the crystallinity of the unexposed sheet to be calculated.
[0212] [Table 47]
[0213] Low power and low speed testing a) A laser with an output of 150 W and a speed of 13 m / min was used.
[0214] The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0215] [Table 48]
[0216] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0217] [Table 49]
[0218] b) A laser with a power output of 75 W and a speed of 8 m / min was used. The spectra were obtained by Raman microscopy analyzing the surface of the specimen at the bottom of the weakened section (known as the "trough").
[0219] [Table 50]
[0220] The formula ΔXc(%) = weakened portion Xc(%) - "reference" Xc(%) was set, and the average value of Xc(%) in the trough of the weakened portion was compared with the average value of the reference Xc(%).
[0221] [Table 51]
[0222] When carrying out the tests of this Example 4 at low power and speed, it was observed that even a low power laser radiation step acting at a low speed makes it possible to provide continuous weakened areas with a reduction in cross section suitable for facilitating the separation of the pots in the weakened areas thus provided. However, from subsequent analysis, it was observed that working under these conditions, an increase in crystallinity was obtained in the weakened areas, and that the variation in crystallinity between the weakened areas and the reference was greater than the value of +3% previously indicated.
[0223] On the one hand, this finding is in agreement with what has been reported in the literature, whereby an increase in crystallinity is associated with an increase in the brittleness of the specimens, and on the other hand, it confirms that the action of the laser beam has an effect on the material that goes beyond a simple reduction in cross section. The application of heat associated with the laser beam and transferred to the material actually gives a variation in the local properties of the material, ranging from a simple variation in the tensile state of the material (high power and high speed laser beam) to an increase in crystallinity (low power and low speed laser beam).
[0224] However, the low operating speeds of the laser (equal to 13 m / min for a 150 W laser and 8 m / min for a 75 W laser), which nevertheless result in the desired separation of the pots from one another, also correspond to long production times for the weakened parts and thus outline a scenario that is not compatible with the need for high industrial productivity.
[0225] In fact, it has been found that the invention achieves its intended aims and objectives by providing a method which is extremely flexible and which makes it possible to provide weakened portions even in containers made of PET, allowing practical and easy separation of the containers from one another.
[0226] In fact, it has been found that the invention achieves its intended aims and objectives and provides a very flexible method that makes it possible to provide weakened portions even in containers made of PET, allowing practical and simple separation of the containers from one another.
[0227] The advantages of the method presented in the present invention can be traced back to the possibility of working with a particularly powerful laser beam emitting system, which makes it possible to solve the problems of manufacturing PET containers in particular, avoid the use of blades or cutters, reduce the costs associated with system maintenance, make use of a very flexible method for providing containers of different shapes and sizes, and have a system that maintains high speeds of industrial production.
[0228] The invention thus conceived is susceptible to numerous modifications and variations, all of which are within the scope of the appended claims, and all details may further be replaced with other technically equivalent elements.
[0229] In fact, the materials used can be any, depending on the requirements and the state of the art, as long as they fit the specific application and the required shapes and dimensions.
[0230] The disclosure of Italian Patent Application No. 102,020,000,000,787, from which this application claims priority, is hereby incorporated by reference.
[0231] Where technical features described in any claim are followed by reference signs, those reference signs are included solely for the purpose of enhancing the comprehension of the claim, and therefore such reference signs do not have any limiting effect on the interpretation of the respective elements identified by such reference signs as examples.
Claims
1. A method for the manufacture and filling of containers designed to contain food, comprising: - shaping a PET (polyethylene terephthalate) sheet (10) to provide a number of storage receptacles (11) provided with at least one access entrance (12), said PET sheet having an initial crystallinity of less than or equal to 10%; - filling said receiving receptacle (11) with at least one food product through said access opening (12); - sealing said access opening (12) by a closing film (13); - providing a weakened portion (21) on a connection edge (22) between at least two adjacent receiving receptacles (11), said providing step comprising emitting a laser beam (40) on at least a portion of said connection edge (22) in order to bring about a local reduction in the cross section of said connection edge (22) along said weakened portion (21); the final crystallinity in the weakened portion (21) after the step of applying the laser beam is equal to or at most 3% lower or higher than the crystallinity in the portion of the connecting edge (22) that is not affected by the modifications resulting from the step of applying the laser beam (40) and the step of sealing the access opening (12); A method comprising:
2. 2. The method of claim 1, wherein the thickness of the connecting edge is between 300 microns and 1800 microns.
3. 3. The method of claim 1 or 2, characterized in that the PET sheet (10) comprises a sheet made of transparent PET.
4. 4. The method of claim 1, wherein the providing step comprises emitting a laser beam having a power output of between 250W and 1500W at a speed of between 15m / min and 170m / min.
5. 5. The method of claim 1, wherein the providing step comprises emitting a laser beam having a power of more than 500 W and a speed of more than 60 m / min.
6. 6. The method according to claim 1, wherein the providing step is adapted to bring about a local reduction in the connection edge that is substantially constant along the longitudinal extension of the weakened portion.
7. 7. The method according to claim 1, wherein the providing step is adapted to provide a plurality of through openings through the connection edge, spaced apart from one another, for providing the weakened portions.
8. The calculation of the crystallinity of the region subjected to the laser beam irradiation step is carried out by performing a Raman microscopy analysis at at least three points of the specimen, and -1 The calibration curve of the average FWHH calculated for signals covering the Raman shift interval 7. A method according to claim 6, characterized in that it is obtained by linear interpolation.
9. 9. The method according to claim 8, characterized in that the area for identifying the at least three points of the test piece for calculating the crystallinity of the area subjected to the radiation step is defined in a lower part ("trough") of the weakened portion (21) when the weakened portion is constant along its longitudinal extension or comprises a local reduction of the connecting edge (22) formed in a solid area equidistant from the through opening of the weakened portion (21) provided with a through opening.
10. 10. A method according to any one of the preceding claims, characterized in that the step of providing a weakened portion (21) is carried out after the step of sealing the access port (12).
11. 11. The method according to any one of claims 1 to 10, characterized in that it comprises a sterilization step carried out upstream or downstream of the thermoforming step.
12. 12. A method according to any one of claims 1 to 11, characterized in that it includes the step of extracting gases and volatile substances substantially during the radiating step.
Citation Information
Patent Citations
PTP package and manufacturing method of the same
JP2006151456A
Cutter and blister packaging machine
JP2018086706A
Method and apparatus for manufacturing resin molding, and resin molding
JP2018187810A
Heat-Resistant Foamed Polyester Articles and Process for Their Manufacture
US20100003378A1